(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article sought to observe the adoption of multimodal resources in the dramaturgical construction of “Why the Child is Coking in the Polenta”, directed by Nelson Baskerville. It is the theater adaptation of the autobiographical novel by Aglaja Veteranyi, a Romanian writer, director and actress who fled to Western Europe with her family during Nicolae Ceausescu’s dictatorship. From a multimodal analysis, with examples commented by Mondada and Lehmann such as the notion of modal density and the use of multimedia in post-dramatic theater, I investigated the aesthetic choices of staging. I considered the importance of reception as an element of realization of the phenomenological question, as the relationship with the public is a fundamental element of contemporary theatrical poetics.